Clinicians’ satisfaction with laboratory services and associated factors at public health facilities in Northeast Ethiopia - Daniel Dagne Abebe; Minwuyelet Maru Temesgen; Addisu Tesfie Abozin (BMC Health Services Research, 2023)
Abstract Background Satisfaction has become a key measure of quality and an important tool for improvement. Laboratories are increasingly required to regularly assess satisfaction of their customers. This study aimed to assess clinicians’ satisfaction with laboratory services and associated factors at public health facilities. Methods A facility-based cross-sectional study was conducted in Northeast Ethiopia from May to June 2019. Eight hospitals and 24 health centres were first selected using a stratified sampling method, and a total of 224 randomly selected clinicians were included. Satisfaction with multiple aspects of laboratory services was assessed using a self-administered questionnaire, on a rating scale of 1 (very dissatisfied) to 5 points (very satisfied). Laboratory quality assessment was performed using WHO-AFRO’s stepwise accreditation checklist. Multivariable logistic regression model was fitted to determine the association between independent variables and clinicians’ overall satisfaction level using STATA ver14.1. A p-value < 0.05 was considered significant. Results Overall, 72.8% of the clinicians were satisfied. Lowest mean ratings were obtained for the helpfulness of the laboratory handbook (3.3), provision of STAT/urgent services (3.7), and adequacy of tests provided (3.8). The clinicians’ timely receipt of results (AOR = 2.3, 95% CI = 1.1–5.0), notification of panic results (AOR = 2.5, 95% CI = 1.1–5.6), perceived quality/reliability of test results (AOR = 3.1, 95% CI = 1.5–6.3), and the laboratories’ rate of concordant malaria microscopy results (AOR = 4.1, 95% CI = 1.8–9.3), were significantly associated with satisfaction. Conclusions Nearly one-third of clinicians were not satisfied with the laboratory services. Laboratory managers should emphasize the timely communication of STAT/urgent and panic results, and the reliability of test results, to improve users’ satisfaction and overall quality of care.